The Ebola virus glycoprotein mediates entry via a non-classical dynamin-dependent macropinocytic pathway - Mulherkar, Nirupama; Raaben, Matthijs; de la Torre, Juan Carlos; Whelan, Sean P.; Chandran, Kartik (Virology (New York, N.Y.), 2011)
Ebola virus (EBOV) has been reported to enter cultured cell lines via a dynamin-2-independent macropinocytic pathway or clathrin-mediated endocytosis. The route(s) of productive EBOV internalization into physiologically relevant cell types remain unexplored, and viral-host requirements for this process are incompletely understood. Here, we use electron microscopy and complementary chemical and genetic approaches to demonstrate that the viral glycoprotein, GP, induces macropinocytic uptake of viral particles into cells. GP's highly-glycosylated mucin domain is dispensable for virus-induced macropinocytosis, arguing that interactions between other sequences in GP and the host cell surface are responsible. Unexpectedly, we also found a requirement for the large GTPase dynamin-2, which is proposed to be dispensable for several types of macropinocytosis. Our results provide evidence that EBOV uses an atypical dynamin-dependent macropinocytosis-like entry pathway to enter Vero cells, adherent human peripheral blood-derived monocytes, and a mouse dendritic cell line.